Evaluation of different techniques for CT radiation profile width measurement. (8th July 2013) - Jackson, Steven R.; Ahmad, Salahuddin; Hu, Yida; Ruan, Chun
Abstract : This work has been conducted to demonstrate a procedure for using a Konica Minolta computed radiography (CR) system for the measurement of computed tomography (CT) radiation profile width, and to compare this method with conventional and GAFCHROMIC XR‐QA2 film measurements. The exposure and processing conditions of a Konica Minolta CR reader system were characterized to establish the relationship between exposure at the imaging plate (IP) and pixel value. A 6 cc ionization chamber was exposed at the isocenter of a CT scanner using 80 kVp, 0.4 sec with various mA settings. CR images were processed in fixed modes with various combinations of S and G values, establishing exposure and pixel value relationships. Appropriate exposure techniques and processing parameters were selected to avoid the saturation of the IP. Using the selected exposure and processing parameters, radiation profiles of various nominal collimation settings (40, 20, 10, and 5 mm) were acquired for measurement. Radiochromic film was characterized and utilized to compare with CR profiles and profiles obtained via conventional film. Appropriate exposures for both CR (80 kVp, large body filter, 4 and 8 mAs) and radiochromic films (120 kVp, large body filter, 300 mAs) were determined. Recommended CR processing settings (fixed mode with S = 5 and G = 1.81 ) were also determined. Compared to the conventional film results, the full width at half maximum (FWHM) results for CR agreed well within ± 10 %, while radiochromic film results showed maximum deviations of about 5%. In conclusion, FWHM of CT radiation profiles can be conveniently and accurately measured using a Konica Minolta CR system or XR‐QA2 film when appropriate exposure technique and processing parameters are used. PACS numbers: 87.57.Q‐, 87.57.qp, 87.59.bd, 87.57.uq